Interfaces in sugar palm fibres reinforced composites: A review - Atiqah A.; Mastura M.T.; Jawaid M.; Sapuan S.M.; Ansari M.N.M. (Elsevier, 2023)
Numerous researches have been conducted on utilising degradable sugar palm that has a good possibility in combination with biodegradable thermoplastic materials. In this paper, recent research of sugar palm particle composites are reviewed. The state of knowledge on the characteristics of the interfaces between sugar palm particles and polymer matrix are presented. The main focus is to relate the interfacial characteristics with sugar palm particle properties. Research methodologies adopted in previous studies on the interfaces are presented. The challenges regarding the interfacial characteristics are also discussed. Moreover, the physical, mechanical, and thermal properties of sugar palm particle composites are reviewed. The recent development of the techniques to characterise sugar palm particles, together with the improvements and limitations of the techniques are also discussed. 2020 Elsevier Ltd. All rights reserved.